Translanguaging Phenomenon In Bilingual People Based On Gita Savitri Youtube Channel - Sunardi Sunardi; Mursyid Anwar; Muhammad Ahsan Tanpubolon (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study focuses on the functions and concepts of translanguaging contained in Gita Savitri Youtube videos. The aims of this study was to find, classify, and analyze the translanguaging functions contained in Gita Savitri ‘Beropini’ videos. The witer used the theory of Jakobson (2001) to identify and analyze the type of translanguaging functions contained in the videos. In addition, the writer also used Wei theory (2017) to identify and analyze the concepts of translanguaging contained in the videos. The writer used descriptive qualitative method to analyze the data while the data were taken from Gita's utterances in both 'Beropini' videos. From the results of this study, the writer found that there were 29 Gita utterances contained translanguaging functions and translanguaging concepts that have been analyzed by the writer. In both videos, the writer only found 3 of the 6 translanguaging functions, namely expressive function, directive function, and referential function. In addition, the writer also found all the concepts of translanguaging that Wei (2017) stated which are translanguaging space and translanguaging instinct.